Dta and x-ray studies on some bio-giasses - Tiwari V.P.; Tyagi B.S.; Nath P. (My University, 2025)
Preliminary studies were carried out on bio-glasses with a view to developing suitable compositions which could be used as orthopaedic implants. Studies to establish conditions necessary for nucleation and proper crystal growth were carried out using DTA and gradient furnace techniques. Ceramization of the glasses was done by thermally treating the glass in such a way as to produce glass-ceramics consisting of more than one microcrystal that were differently oriented. The crystallized samples were put to X-ray analysis, scanning and transmission electron microscopy in order to find out the type and the size of the crystals. This study mainly pertains to the glass-ceramics composed of primarily Na20-Ca0-Si02 and P20 5 in suitable composition ranges. Inthe present communication, the data pertaining to the studies on nucleation and crystallization of some glasses have been reported. © 1986 Taylor & Francis Group, LLC.